Genetic Factors in Rasmussen’s Encephalitis Characterized by Whole-Exome Sequencing - Ai, Junhong; Wang, Yisong; Liu, Dong; Fan, Dongying; Wang, Qiqi; Li, Tianfu; Luan, Guoming; Wang, Peigang; An, Jing (Frontiers in Neuroscience, 2021)
Rasmussen's encephalitis (RE) is a rare chronic neurological disorder characterized by unihemispheric brain atrophy and epileptic seizure. The mechanisms of RE is complex. Adaptive immunity, innate immunity and virus infection were all involved in the development of RE. However, there is few studies about the role of genetic factors in the mechanisms of RE. Thus, the objective of this study is to reveal the genetic factors in the mechanisms of RE. Whole-exome sequencing (WES) was performed in 15 RE patients. 10 patients with temporal lobe epilepsy (TLE) which is a common and frequently intractable seizure disorder was used as the control. Thirty-one non-silent single nucleotide variants (SNVs) affecting 16 genes were identified in RE cases. The function of genes with SNVs were associated with antigen presentation, antiviral infection, epilepsy, schizophrenia and nerve cell regeneration. Genetic factors of RE were found firstly in this study. It suggested that RE patients have congenital abnormalities in adaptive immunity and are susceptibility to some harmful factors, which lead to a polygenic abnormal disease.